Impact of volcanic ash deposition on foliar productivity and insect herbivory in northern Patagonia deciduous forests - Chaneton, Enrique Jose (2014)
Volcanism has been a major force shaping the dynamics of Andean landscapes during the Holocene. Yet we still know little about the consequences of modern volcanic events on forest functioning. Ash fall may elicit multiple direct and indirect effects on key ecosystem attributes, with disturbance severity likely varying with distance to the crater. We examined the impact of ash deposition on foliage productivity and insect herbivory after the 2011 eruption of the Volcán Puyehue-Cordón Caulle system, in Nothofagus pumilio forests of northern Patagonia, Argentina. Tree leaf litterfall, a surrogate for annual foliar production, was measured before and after the event in wet and dry forest sites, which were located 22 km and 80 km east from the crater and were affected by mass deposition of coarse- and fine-grained tephra, respectively. Leaf damage by insects was monitored over a 10-year span (2004-2013) including the volcanic event. Foliar productivity in 2012 dropped by 60% in the wet forest, but did not change in the dry forest. Leaf area damaged by insects decreased abruptly in 2012, with post-eruption herbivory levels falling outside the range of annual variation recorded before the event. The impact was most severe in the dry forest wich normally supports the highest endemic herbivory. In contrast, leaf damage remained high in another dry forest located 98 km southeast from the crater and little affected by ashfall. Changes in foliar production and insect herbivory persisted for two years after the event. Our results show a widespread disruption of canopy-herbivore interactions in areas heavily affected by tephra. Remarkably, volcanic ash acted as a broad-spectrum insecticide on canopy herbivores. In the short-term, ashfall constrained the energy flow through the forest canopy and the arthropod consumer community, and thus temporarily overwhelmed previously existing differences in productivity and herbivory between wet and dry forest habitats.